2021
DOI: 10.1158/2767-9764.crc-21-0060
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Immunoprofiling of High-Risk Oral Proliferative and Localized Leukoplakia

Abstract: Oral leukoplakia is common and may, in some cases, progress to carcinoma. Proliferative leukoplakia is a progressive, often multifocal subtype with a high rate of malignant transformation compared with the more common localized leukoplakia. We hypothesized that the immune microenvironment and gene expression patterns would be distinct for proliferative leukoplakia compared with localized leukoplakia. We summarize key clinicopathologic features among proliferative leukoplakia and localized leukoplakia and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…A recent comprehensive study of patient samples of leukoplakia identified that proliferative leukoplakia predicts a high rate of malignant transformation within 5 years of diagnosis. Interestingly, CD8 + T cell and Treg signatures with PD-L1 overexpression provides a justified approach to use anti-PD1 as immunoprevention approach in oral leukoplakia ( 124 ). Since these hydrogels are topically applied similar to TLR agonists used in melanoma, this platform provides an approach to incorporate additional immune agonists alone or to be used to increase the efficacy of checkpoint blockade.…”
Section: Reversing Immunosuppression In Oplmentioning
confidence: 99%
“…A recent comprehensive study of patient samples of leukoplakia identified that proliferative leukoplakia predicts a high rate of malignant transformation within 5 years of diagnosis. Interestingly, CD8 + T cell and Treg signatures with PD-L1 overexpression provides a justified approach to use anti-PD1 as immunoprevention approach in oral leukoplakia ( 124 ). Since these hydrogels are topically applied similar to TLR agonists used in melanoma, this platform provides an approach to incorporate additional immune agonists alone or to be used to increase the efficacy of checkpoint blockade.…”
Section: Reversing Immunosuppression In Oplmentioning
confidence: 99%
“…In OPMD, the accumulation of immune cells is commonly observed in dysplastic areas (14)(15)(16)(17). Common changes reported in the immune microenvironment of OPMD are similar to other premalignant lesions, including CD3 lymphocytes, CD8 T cells, T regulatory (Treg) cells, M1/M2macrophages and the PD-1/PD-L1 axis (12,13,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, knowledge on the immune profile of OPMD remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…33 A recent spatial immune analysis in patients with a clinically distinct, extremely high-risk oral proliferative leukoplakia also observed a strong correlation of high PD-L1 scores predicting worse OCFS. 34 Although not the central driver in mediation analysis of LOH and dysplasia (Tables S1 and S2), our data suggest that PD-1/PD-L1-mediated immune evasion contributes, to some extent, to the invasive-disease transition in progression of oral oncogenesis, and therefore, provides strong rationale for PD-1/PD-L1 axis blockade in high-risk PD-L1-positive patient subgroups.…”
Section: Discussionmentioning
confidence: 73%
“…Our results are consistent with two recent, small, OPC, retrospective reports of higher cancer risk: in a study of eight patients (out of 120) with cancer, PD‐L1 expression (scored qualitatively, intensity = 2 vs. 0, 1) was found to be a predictor of OPC OCFS; 16 and in a recent cross‐sectional, case‐control study of 39 total patients, of which 19 were cases with cancer, increased PD‐L1 expression was observed in progressing versus non‐progressing dysplasias 33 . A recent spatial immune analysis in patients with a clinically distinct, extremely high‐risk oral proliferative leukoplakia also observed a strong correlation of high PD‐L1 scores predicting worse OCFS 34 . Although not the central driver in mediation analysis of LOH and dysplasia (Tables S1 and S2), our data suggest that PD‐1/PD‐L1‐mediated immune evasion contributes, to some extent, to the invasive‐disease transition in progression of oral oncogenesis, and therefore, provides strong rationale for PD‐1/PD‐L1 axis blockade in high‐risk PD‐L1–positive patient subgroups.…”
Section: Discussionmentioning
confidence: 91%